Study of Cardiovascular Risk Markers in Type 2 Diabetes Mellitus with Obesity - Ramya.S; Sureka Varalakshmi.V; Uma maheswari .K; Chandan Bala.R (International Journal of Pharma and Bio Sciences, 2020)
Obesity and overweight account for 44% of the Type 2 Diabetes Mellitus cases and an increase in body weight lead to various complications. Type 2 Diabetes Mellitus (T2DM) is most strongly associated with obesity, and the world wide prevalence of obesity-related diabetes is expected to double to 300 million by 2025. We planned to study the association of TSH (Thyroid Stimulating Hormones) and other markers such as Hs CRP, GGT in T2DM. Patients classified based on BMI. The study includes 130 T2DM patients, among them 27 T2DM patients were Obese (Group A), 52 T2DM patients were overweight (GroupB) and 51 T2DM patients with normal BMI (Group C). Statistical analysis was doneby using SPSS 17 version. Data were presented as mean ± standard deviation. Differences among groups were calculated using one way ANOVA/or Kruskal-Wallis Test was used.. Mean values of FBS, HbA1C, Hs CRP, and TSH were significantly higher among participants of Group A than Group B and C. GGT (Gamma glutamyl transferase) show higher mean value in group B. FBG is highly significant in obese and overweight (Group A and B) when compared with normal BMI subjects, whereas HbAIc shows a significant difference in overweight (Group B) when compared with normal BMI subjects. HsCRP shows significance in Obese (Group A) with normal BMI group. GGT shows significance in overweight (Group B) with normal BMI subjects and TSH shows a significant difference in obesity (Group A) with overweight and normal BMI subjects. It is concluded that increased levels of High sensitive C Reactive protein. Gamma glutamyl transferase and Thyroid stimulating hormones are associated with obesity and overweight in subjects with T2DM and these variables can be used as a marker to predict the onset of cardiovascular diseases.